Optimization of patch-wise laminated composite panels for enhanced dynamic characteristics. (1st August 2021) - Lee, Chanhui; Greenhalgh, Emile S.; Panesar, Ajit
Abstract: Fiber-reinforced laminated composites are widely utilized in the transportation industries due to their superior specific stiffness and strength over conventional metals. The most widely used forms of fiber-reinforced composites are in a laminated plate panel. The inherent anisotropy of composites and the associated dynamic loading characteristics make the design process for such a structure very challenging. In particular, the composite panels used for ship structures must be lightweight and robust enough to withstand external dynamic loads such as wave loads. In this study, we present a two-level optimization strategy to improve the modal dynamic stiffness of laminated composite panels utilising lamination parameters and a patch-wise lay-up approach. Numerical results showed a significant increase in fundamental natural frequency and specific dynamic stiffness compared to the quasi-isotropic design.